Multi-disciplinary performance studies on propulsion system integration for military aircraft. - Antonakis, Aristeidis (Cranfield University, 2019)
Military aircraft propulsion systems represent one of the most challenging sectors of jet engine design: Operating at an extremely variable environment strongly influenced by aircraft aerodynamics, these engines should pack high thrust output at the minimum possible size without compromising reliability and operating cost. In addition, the multidisciplinary nature of military aircraft operations frequently introduces contradicting performance objectives which are hard to incorporate to engine design. All the above are combined with the very high cost of engine development, necessitating proper selections early in the design phase to ensure the success of the development process and the viability of new engine concepts. Despite the significant volume of research in the field and perhaps due to the sensitivity of the data involved, studies published to date are focused on rather specific topics without addressing the full multidisciplinary aircraft-propulsion system integration problem. In order to achieve this, a new synthesis of methods needs to be established combining aspects and contributions from different areas of research. This project investigates the development of a new methodology for interconnecting engine preliminary design to aircraft operational requirements. Under this scope, a representation of a generic military airframe is constructed and combined with engine performance models and simulation tools to investigate propulsion system effects on aircraft mission performance and survivability. More specifically, the project’s contributions in the field of military aircraft propulsion system integration are focused on three domains: • A new military aircraft representation modelling critical aspects of the interaction between the aircraft and the propulsion system: Aircraft aerodynamics, airframe/propulsion system aerodynamic interference, IR and noise signature. The model has low computational requirements and is suitable for use in the context of large-scale parametric studies and trajectory optimization cases. • New simulation-based techniques for estimating climb performance and assessing the mission capabilities of aircraft/engine configurations in realistic mission scenarios. Points of novelty within the developed methods include a multi-objective formulation to the climb trajectory problem, a technique for Altitude-Mach tracking, an expansion of the Energy-Manoeuvrability (E-M) technique allowing for the concurrent optimization of the aircraft trajectory and engine schedule and the introduction of minimum noise and IR trajectories for military aircraft. • The quantification of propulsion system effects on aircraft survivability, taking into account both the aircraft’s IR signature and aircraft/missile kinematic performance. This is achieved through a combination of an aircraft IR model with kinematic simulations of missile-vs-aircraft and aircraft-vs-aircraft which are used to measure an aircraft’s susceptibility to attacks, along with its own ability to attack manoeuvring targets. The above methods are developed and validated using published data and applied to investigate aircraft performance trends in a series of test cases where the effectiveness of different propulsion system designs is evaluated in a variety of simulated mission tasks. The results successfully demonstrate the developed methods’ ability to quantify the relation between aircraft performance and engine design, providing a basis for understanding the performance trade-offs that result from the adoption of different propulsion system configurations, to maximize the efficiency of the powerplant design process.
Keywords: Survivability; trajectory; optimization; IR signature; climb performance; propulsion